Ethopolitics and the Financial Citizen. Issue 1 (February 2014) - Pathak, Pathik
While personal debt has been the subject of intense research activity over the past decade, in particular from think tanks and government bodies, it remains relatively undertheorized and neglected in general by the social sciences. This article offers a novel theoretical frame for the analysis of personal debt – and personal overindebtedness in particular – by highlighting the construction of deviance from financial behavioural normativities. Using Nikolas Rose's concept of 'ethopolitics' to describe the relocation of government from questions of rational administration to those of everyday morality and ethics, this article presents two characterizations of deviance from an ethopolitical imaginary of financial citizenship: irresponsibility and incapability. From this framework, the article explores the nature of the state sponsored normalization of indebtedness and the stigmatization of overindebtedness as a corollary of 'delinquent' dispositions and dependencies. This article suggests that UK government policy concerning financial responsibility has been shaped by an ethopolitical imaginary of financial citizenship which is based upon a skewed understanding of structure and agency which has its parallel in the attribution of unemployment to 'worklessness'.